THE IMPACT OF EARLY MARRIAGE ON YOUNG WOMEN - Sirait, Rini Anjelina (Journal of Psychiatry Psychology and Behavioral Research, 2025)
Introduction: Women who marry young experience enormous pressure when problems arise in marriage because they are emotionally and psychologically unprepared, underage, and encouraged to become precocious. This paper aims to review the impact of early marriage, specifically on young women. Methods: The research method employed in this article utilizes a literature review approach, where data derived from literature and document searches are analyzed descriptively. Results: Study of the influence of conflict in young marriages based on research findings, in addition to having negative psychological effects, there are also positive effects in marriage. Discuss: The problems of quarrels that may arise in a husband-and-wife relationship and how to handle them are difficult to overcome due to their immature nature, thinking style, and emotional instability, which can sometimes affect women's mental health. Conclusion: marriage is building a family and starting to establish communication, commitment, economic needs, knowing personality, adjustment, and love (affection). Poor communication between husband and wife, lack of commitment in the relationship, lack of financial independence and still receiving financial support from each other's parents, and lack of understanding of the couple's personality by the wife all have an impact on the quality of the marriage.